The Ordering Distribution and Competing Motivation of Evidential and Logical Causal Clauses in English and Chinese - Fu, Wanying (OKARA: Jurnal Bahasa dan Sastra, 2024)
The ordering distribution of causal adverbial clauses in English and Chinese differs due to distinct factors, with English clauses tending to appear finally and Chinese clauses initially. This study aims to analyze the ordering distribution of logical and evidential causal clauses in English and Chinese using Diessel’s competing motivation model, investigating the interplay of semantic forces, syntactic processing, and discourse pragmatics. A corpus-based analysis was conducted on 800 sentences from the British National Corpus and the Lancaster Corpus of Mandarin Chinese, focusing on four causal subordinators in each language. The results reveal a clear cross-linguistic distinction: In Chinese, evidential causal clauses occur initially at 82.5%, driven by iconicity and discourse coherence, while logical causal clauses show a lower initial occurrence rate of 67.3%. Conversely, English causal clauses tend to occur in final positions, with evidential clauses at 91.66% and logical clauses at 84.2%, due to the relative semantic independence, functioning as independent processing units. The ordering distribution reflects competing motivations: Chinese prioritizes iconicity and discourse coherence, while English emphasizes syntactic independence and processing ease. The study provides new insights into the interaction of semantic, syntactic, and pragmatic forces in shaping clause positioning across languages.